An innovative 'simultaneous' bilingual approach in Senegal: promoting interlinguistic transfer while contributing to policy change. Issue 4 (21st April 2022) - Benson, Carol
ABSTRACT: This paper describes an innovative bilingual education program developed and implemented in 208 primary classes in Senegal from 2009 to 2018 by a Senegalese NGO working with the national Ministry of Education to address issues of quality in primary education. L'approche simultanée or simultaneous approach, also known as bilinguisme en temps réel or real-time bilingualism, developed organically through a consultative process between NGO development actors, university linguists and educators. Unlike the early-exit transitional bilingual programs previously piloted in Senegal that are common throughout West Africa, this program taught literacy, mathematics and the sciences in both a national language (Wolof or Pulaar) and French from the first year of primary school. Using data collected for an external evaluation conducted in 2018, along with follow-up research conducted in 2019 with designers and implementers of the simultaneous approach, this paper analyzes the effectiveness of the program and its implications for Senegal, where the Ministry of Education appears close to adopting a national language-in-education policy. There are also implications for the field of L1-based multilingual education, as ARED's simultaneous approach provides a refreshing new perspective on teaching and learning non-dominant and dominant languages.